Global development assistance for early childhood care and education in 134 low- and middle-income countries, 2007-2021 - Luan, Y; Hodgkin, D; Behrman, J; Stein, A; Richter, L; Cuartas, J; Lu, C (2024)
Providing quality early childhood care and education (ECCE) is widely recognized as a fundamental strategy for lifelong individual and societal benefits. However, the expansion of ECCE in low- and middle-income countries (LMICs) is impeded by limited financial resources. Little is known about the levels and trends of global development assistance (DA) allocated to ECCE in LMICs between 2007 and 2021. We extracted data from the Creditor Reporting System (CRS) on aid projects in 134 LMICs from 2007 to 2021. Using keyword-searching and funding-allocation methods, we generated two estimates of ECCE aid: one for DA primarily focused on ECCE, and another for DA both primarily and partially focused on ECCE as well as DA not explicitly targeting ECCE but benefiting ECCE. We analyzed the patterns and time trends of ECCE aid by donors, recipients, CRS sectors, implementing agencies, and aid-flow types. We calculated ECCE aid as a percentage of educational aid at both annual and aggregative levels, comparing it to UNICEF’s recommended allocation of at least 10% of educational aid to the ECCE sector in LMICs. Additionally, we explored the alignment of aid with addressing children’s learning losses during global crises by examining ECCE aid to projects involving COVID-19 prevention and mitigation, along with ECCE aid to conflict-affected countries. From 2007 to 2021, primary ECCE-focused DA amounted to US dollars 3,646 million, accounting for 1.7% of the total US dollars 213,279 million allocated to education. The World Bank led all donors with US dollars 1,944 million in ECCE aid (53.3%). Low-income countries consistently received less ECCE aid per child before 2016, then started to catch up, but subsequently experienced a decrease from US dollars 0.8 (2020) to US dollars 0.6 (2021). In contrast, lower-middle-income and upper-middle-income countries saw an increase from US dollars 0.4 (2020) to US dollars 0.6 (2021) and from US dollars 1.0 (2020) to US dollars 1.3 (2021), respectively. ECCE aid to projects with COVID-19 activities declined from US dollars 50 million in 2020 to US dollars 37 million in 2021, representing 11.4% and 6.6% of annual ECCE aid. Over 15 years, conflict-affected countries received an average of US dollars 0.3 per child, only a quarter of the aid received by non-conflict-affected countries (US dollars 1.2 per child). Although ECCE aid increased significantly between 2007 and 2021, its share of total educational aid remained small and fell far short of the recommended minimum of 10%. Our recommendations include increasing the share of ECCE aid in total educational aid, raising aid to low-income and conflict-affected countries, and investing more in preparing ECCE programs for future global crises.